Os discursos do etnólogo, do filósofo e do ficcionistana estrutura do romance Nove noites - Cid Ottoni Bylaardt (Estudos de Literatura Brasileira Contemporânea)
This paper intends to establish a dialogue between two texts: “Structure, Signand Play in the Discourse of Human Sciences”, by Jacques Derrida, andNovenoites[Nine nights] by the Brazilian contemporary novelist Bernardo Carvalho.Derrida‟s text seems tohold the origins of the deconstructionist thinking of thephilosopher, and begins with an aporia pointed by Lévi-Strauss in the binarypair nature-culture to discuss the centered model of the occidental thinking.This scandal, thus, is associated to the activity of the ethnologist and has itsroots in ethnography. This text seeks, therefore, to reflect upon how the fictionseizes the discourse of human sciences in order to put it in question, in amovement similar to Derrida‟s thinking in the permanent deconstructionism‟sinterpellation to the scientific discourse. The narrative, which at first seemed tolead to the solution of a crime, like in a detective story, frustrates the reader‟sexpectations, dissolving what seemed to be a consistent trajectory of astructureerected around a solid center.